Shock deformation in zircon grains from the Mien impact structure, Sweden. (12th February 2021) - Martell, Josefin; Alwmark, Carl; Holm‐Alwmark, Sanna; Lindgren, Paula
Abstract: Recognition of impact‐induced deformation of minerals is crucial for the identification and confirmation of impact structures as well as for the understanding of shock wave behavior and crater formation. Shock deformed mineral grains from impact structures can also serve as important geochronometers, precisely dating the impact event. We investigated zircon grains from the Mien impact structure in southern Sweden with the aim of characterizing shock deformation. The grains were found in two samples of impact melt rock with varying clast content, and in one sample of suevitic breccia. We report the first documentation of so‐called "FRIGN zircon" (former reidite in granular neoblastic zircon) from Mien (pre‐erosion diameter 9 km), which confirms that this is an important impact signature also in relatively small impact structures. Furthermore, the majority of investigated zircon grains contain other shock‐related microtextures, most notably granular and microporous textures, that occur more frequently in grains found in the impact melt than in the suevitic breccia. Our findings show that zircon grains that are prime candidates for establishing a new and improved age refinement of the Mien impact structure are present in the impact melt.